Development of a Novel Ceramic Support Layer for Planar Solid Oxide Cells. Issue 2 (13th February 2014) - Klemensø, T.; Boccaccini, D.; Brodersen, K.; Frandsen, H. L.; Hendriksen, P. V.
Abstract The conventional solid oxide cell is based on a Ni–YSZ support layer, placed on the fuel side of the cell, also known as the anode supported SOFC. An alternative design, based on a support of porous 3YSZ (3 mol.% Y2O3–doped ZrO2), placed on the oxygen electrode side of the cell, is proposed. Electronic conductivity in the 3YSZ support is obtained post sintering by infiltrating LSC (La0.6Sr0.4Co1.05O3). The potential advantages of the proposed design is a strong cell, due to the base of a strong ceramic material (3YSZ is a partially stabilized zirconia), and that the LSC infiltration of the support can be done simultaneously with forming the oxygen electrode, since some of the best performing oxygen electrodes are based on infiltrated LSC. The potential of the proposed structure was investigated by testing the mechanical and electrical properties of the support layer. Comparable strength properties to the conventional Ni/YSZ support were seen, and sufficient and fairly stable conductivity of LSC infiltrated 3YSZ was observed. The conductivity of 8–15 S cm–1 at 850 °C seen for over 600 h, corresponds to a serial resistance of less than 3.5 m Ω cm2 of a 300 μm thick support layer.